A survey-based study of challenges of multilingualism in Pakistan - Atifa Nisa; Zamna Sarfraz; Amber Naveed; Farah Mahmood (Universitas Syiah Kuala, 2023)
This paper aims to investigate how people face different challenges in a multilingual and multicultural society, especially in Pakistan. The English enjoys official language status, while Urdu is the national language in Pakistan. Minority languages, on the other hand, are a sign of stigma and destitution, and most speakers of minority languages face discrimination. In this paper, a binary approach of qualitative and quantitative is used to explore multilingualism in Pakistan. In order to understand how Pakistan's language policy favors some languages over others and what impact that has appeared on politics, society, education, and the economy. A closed-ended questionnaire was given to 30 participants as part of the quantitative data gathering process utilizing the purposive sampling technique. In the qualitative phase, researchers used content analysis as a strategy to gather information from secondary sources in search of strategies and solutions to the challenges. It also briefly examines the effects of globalization on Pakistani languages. The findings of the study revealed that there is a need to use such strategies that help overcome these challenges and help in the development of English as an international language. Future researchers can undertake a longitudinal study to investigate the language development and experiences of multilingual persons in Pakistan and they can perform a comparative examination of multilingualism in various regions of Pakistan.